Peran Sosial Media Instagram Dan Tiktok Pada Brand Image Dan Jaringan Bisnis Jewelry Beads - Resya Dwi Marselina; Dellya Putri; Kania Kania; Nazillah Layla Nur K; Novia Wulan (Institut Nalanda, 2024)
The purpose of this research is to find out about the role of social media Instagram and TikTok on the brand image and business network of Jewelry Beads. This research uses a descriptive qualitative research method. The object of this research is the Jewelry Beads business. The results of this research are the strategy carried out by Jewelry Beads in improving its brand image, namely by creating social media, the strategy carried out by Jewelry Beads in expanding its business network, namely by maintaining good communication with various institutions, the role of social media Instagram and TikTok in the Jewelry Beads business is to improve the brand image and business network, apart from that, so that it can be known by the wider community and also to maintain communication both with partners and customers.